Variations in Toxic Metal Levels of Two Fish Species, Pomatomus saltatrix and Dicentrarchus labrax, and Risk Estimation for Children - Yaman, Mehmet; Yaman, Ibrahim H. (Office Spectroscopy & Spectral Analysis, 2014)
The concentrations of five toxic metals were monthly determined in two fish species, obtained from fish markets in Turkey during 2010-2011. For the determinations, AAS and ICP-AES were used. The obtained lead concentrations for all studied Pomatomus saltatrix (mean 635 mu g center dot kg(-1)) and Dicentrarchus labrax (mean 463 mu g center dot kg(-1)) samples were found to be significantly higher than the maximum allowances concentration (MAC) of 300 mu g center dot kg(-1). Mean chromium (324 mu g center dot kg(-1)) and Cu (940 mu g center dot kg(-1)) concentrations in Pomatomus saltatrix were higher than in Dicentrarchus labrax (268 mu g Cr center dot kg(-1) and 600 mu g Cu center dot kg(-1)) while Ni in Pomatomus saltatrix (216 mu g center dot kg(-1)) was lower in Dicentrarchus labrax (291 mu g center dot kg(-1)). The estimated non-carcinogenic and carcinogenic health risks by the Target Hazard Quotient and target carcinogenic risk indicate that there are no sytemic effects, and the risk of developing cancer over a human lifetime is between 2 similar to 9 in 1 000 000.
Keywords: Toxic metals; Fish; Atomic absorption; ICP-AES; Risk assessment